Configural properties of face portraits change between childhood and adulthood. (January 2023) - Balas, Benjamin; Weigelt, Sarah; Koldewyn, Kami
Adult observers are sensitive to the configuration of facial features within a face, able to distinguish between relative differences in feature spacing, and detecting deviations from typical facial appearance. How does the representation of the typical configuration of facial features develop? While there is a great deal of work describing children's developing abilities to detect differences in feature spacing across face images, there is substantially less work examining what children think constitutes a typical arrangement of facial features. In the current study, we investigated this issue using a production task in which adults and 5- to 10-year-old children created a face "portrait" by arranging the eyes, nose, and mouth of a standard face within an empty outline. Using this simple task, we found differences in face configuration across age groups, such that children of all ages made far larger errors than adult participants, expanding facial features outward from the center of the face more than adults. These results were not affected by face inversion, potentially implying a domain-general rather than face-specific process. We also found that children of all ages endorsed the correct configuration as a best likeness in a perceptual task. We discuss these results in terms of ongoing debate regarding the extent to which configural processing is a meaningful component of face recognition and the conclusions we can draw from production paradigms as compared to purely perceptual tasks.